2020
DOI: 10.1016/j.maturitas.2020.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for housebound older persons during the Covid-19 pandemic

Abstract: Targeting older at-risk patients with decision-making algorithms is a priority at a time when hospitals are receiving an influx of Covid-19 patients that may exceed their capacity. Such screening could likely be extended to primary care settings in order to identify older community dwellers with Covid-19, but also those experiencing the adverse consequences of prolonged home confinement. The Centre of Excellence on Longevity of McGill University (Quebec, Canada) designed a short assessment for Montreal's house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…Fourteen studies identified the impacts of COVID-19 on primary care service provision [ 19 , 22 , 29–33 , 35 , 36 , 38 , 42 , 44 , 45 ]. Impacts were classified under the sub-themes: reduced capacity of/access to primary care, reduced quality of primary care, and patients’ avoidance or delaying of non-COVID care.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies identified the impacts of COVID-19 on primary care service provision [ 19 , 22 , 29–33 , 35 , 36 , 38 , 42 , 44 , 45 ]. Impacts were classified under the sub-themes: reduced capacity of/access to primary care, reduced quality of primary care, and patients’ avoidance or delaying of non-COVID care.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles (13/34; 38.2%) proposed older peoplefriendly policies and systems-strengthening approaches that would lead to improvements in the availability, accessibility, affordability, and quality of telehealth services. [61,73,85,91,94] Make an informed decision to use telehealth for health care services assessing the pros and cons [44,52,68,70] Discuss concerns with health care providers and explore solutions to mitigate concerns [70] Be part of blended communities that bring together online and in-person activities [91,99] Be involved in the process of standardization of telehealth use for geriatric care [70,85] Physicians and Other Health Care Providers Get trained in assessing patients using video conference [52] Convert current in-person screening and diagnostic tools into digital versions [52] Dedicate time in asking patients questions about concerns and barriers to accessing technology [93] Redirect patients to educational community resources for telehealth use when necessary [95] Technology Develop automatic speech analysis to diagnose and monitor dementia [82] Improve technology to accommodate age-related sensory and cognitive impairment [46,63,64,94] Replace ambiguous/technical jargon with easily understandable terms [64,100] Develop larger touchscreen tablets to make visual acuity less of a barrier [64,94] Use a simple and timely back-up process in the event of equipment or connectivity failure [70,97] Address hacking risk by ensuring the use of secure software [70] Governance/Health Systems Provide educational outreach to support older adults to use digital devices [87,91,94] Ensure sanitization of telemedi...…”
Section: O-opportunitiesmentioning
confidence: 99%
“…Telemedicine programs may offer the possibility to deal with these aspects related to the social distancing [ 10 , 25 ]. In the last months, several initiative focused on telehealth in community-dwelling older adults have been set up, also solicited by national health authorities, to offer adequate support to this frail population [ 26 , 27 ]. For example, Beauchet et al developed a telephone screening test named “Evaluation SOcioGERiatrique” (ESOGER) which included assessment of: (1) COVID-19 manifestation; (2) frailty; (3) psychological distress; (4) social isolation and (5) caregivers’ burden, to early detect homebound older adults at risk of negative outcomes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%